Implementasi Data Mining Menggunakan Neural Network Untuk Prediksi Penjualan (Studi Kasus: Burjo Burneo Seturan Raya) - Detuer Wonda; Irfan Pratama (Universitas Mercu Buana Yogyakarta, 2023)
Abstract Burjo burneo is effort business that sells various type product food and drink with fast serve. distribution process stock product conducted after inventory in warehouse _ _ run out. With supplier Process product like this precisely often affect _ profit targeted profit. Algorithm Neural Network so one solution alternative for manager for predict to sale goods for period time next with using sales data before. Prediction process started make modeling on rapidminer with hidden parameter conditions layer 3 and learning rate 0.03, next the model already formed will continued the running process for produce score desired prediction. _ Destination from prediction this is for look for score root mean square error (RMSE) with performance best for each input data. rmse is level error results regression, meaning the more small score rmse approach digit 0, then results regression will the more accurate. Sehinnga results from study this score accurate performance error _ obtained as big as 0.025.